2015
DOI: 10.1111/inm.12128
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a smoke‐free policy in an inpatient psychiatric facility: Patient‐reported adherence, support, and receipt of nicotine‐dependence treatment

Abstract: The implementation of smoke-free policies in inpatient psychiatric facilities, including patient adherence, mental health nursing staff support, and provision of nicotine-dependence treatment to patients, has been reported to be poor. The extent to which the quality of smoke-free policy implementation is associated with patient views of a policy is unknown. We conducted a cross-sectional survey of 181 patients (53.6%, n = 97 smokers; and 46.4%, n = 84 non-smokers) in an Australian inpatient psychiatric facilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(39 citation statements)
references
References 28 publications
(32 reference statements)
2
36
0
1
Order By: Relevance
“…Despite the existence of guidelines, the literature indicates that smoking cessation care is not routinely provided to smokers with a mental illness in inpatient (Prochaska et al, 2004;Wye et al, 2010a) or community (Anderson et al, 2013;Bartlem et al, 2015;Bartlem et al, 2014) mental health services and smoking cessation supports such as Quitline referral and nicotine replacement therapy are not routinely provided (Anderson et al, 2013;Bartlem et al, 2015;Bartlem et al, 2014). In GP, suboptimal smoking cessation care has been reported to be provided to both general and mental health patients (Holmberg et al, 2014;Lord et al, 2010;McKayBrown et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Despite the existence of guidelines, the literature indicates that smoking cessation care is not routinely provided to smokers with a mental illness in inpatient (Prochaska et al, 2004;Wye et al, 2010a) or community (Anderson et al, 2013;Bartlem et al, 2015;Bartlem et al, 2014) mental health services and smoking cessation supports such as Quitline referral and nicotine replacement therapy are not routinely provided (Anderson et al, 2013;Bartlem et al, 2015;Bartlem et al, 2014). In GP, suboptimal smoking cessation care has been reported to be provided to both general and mental health patients (Holmberg et al, 2014;Lord et al, 2010;McKayBrown et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…All socio-demographic, clinical, and smoking characteristic items were adapted from previous research (Bartlem et al, 2015). Items detailing the perceived mental health effects of smoking, attitudes to smoking bans in specialist mental health services, and expectations of smoking cessation care provision were developed for the current study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, it has been shown that inpatients often do not receive optimal levels of NRT and that psychiatric nurses do not feel adequately trained to provide NRT effectively (Hollen et al ., ; Ratschen et al ., ; Stockings et al. ; Wye et al . ; Wye et al .…”
Section: Critical Examination Of Arguments Against Smoke‐free Mental mentioning
confidence: 99%